CHANGE OF THE ROLE OF THE OIL COMPLEX IN STRUCTURE OF WORLD POWER BALANCE IN THE CONDITIONS OF GLOBALIZATION OF INTERNATIONAL ECONOMIC RELATIONS - E. Mahankov (Вестник университета)
The article is devoted to research of a role of an oil complex in world power balance. Tendencies of change of supply and demand in the world market of oil are revealed. Globalization tendencies in world oil production are estimated. Features of transformation of the market at the present stage are defined.